2006
DOI: 10.1111/j.1440-1746.2006.04317.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of concurrent elemental diet on infliximab treatment for Crohn’s disease

Abstract: Infliximab was clinically useful in the treatment of Crohn's disease in Japanese patients as well as in those in Western countries. The efficacy of concurrent ED was suggestive and should be confirmed in a randomized controlled study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
34
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 27 publications
1
34
0
1
Order By: Relevance
“…Elemental diet therapy (ED) is high-calorie liquid diets containing primarily amino acids that are absorbed by the small intestine without digestion, and was originally developed as food for astronauts who worked for the National Aeronautics and Space Administration in the 1960s [47].…”
Section: Impact Of Diet On Treatment Results From Anti-tnf Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Elemental diet therapy (ED) is high-calorie liquid diets containing primarily amino acids that are absorbed by the small intestine without digestion, and was originally developed as food for astronauts who worked for the National Aeronautics and Space Administration in the 1960s [47].…”
Section: Impact Of Diet On Treatment Results From Anti-tnf Treatmentmentioning
confidence: 99%
“…In a retrospective study of primary response in 110 CD patients that received either one single infusion (luminal disease) or three infusions (fistulising disease) with the anti-TNFα drug Infliximab (IFX), 51 patients concomitantly received ED [47]. CD activity index (CDAI) was assessed and CDAI < 150 was defined as clinical remission.…”
Section: Impact Of Diet On Treatment Results From Anti-tnf Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…EN is used as both an induction and maintenance treatment (Takagi et al 2006). There are some reports that showed the efficacy of combination therapy of IFX and nutritional therapy (Matsumoto et al 2005;Tanaka et al 2006). Matsumoto et al showed that IFX was effective under TPN or EN (Matsumoto et al 2005).…”
mentioning
confidence: 99%
“…Matsumoto et al showed that IFX was effective under TPN or EN (Matsumoto et al 2005). Tanaka et al showed that CD patients with concurrent ED had a significantly higher response rate to IFX than those without EN (Tanaka et al 2006). However, there are no reports that have compared the effects on mid-and longterm prognosis among the induction and maintenance thera-pies used in Japan, especially between infliximab and EN.…”
mentioning
confidence: 99%